2016
DOI: 10.5505/jems.2016.36744
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of the Number of Tugboats in the Area of Towage Service Authorization by Using Simulation Modelling Technique

Abstract: Öz Römorkörcülük hizmeti verecek bir teşkilatın ilk yatırım maliyetlerinin oldukça yüksek

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In one of the simulation studies focusing entirely on towage services, Nas 1 aimed to determine the optimum parking locations of tugboats belonging to an organization providing towage services in a port in Turkey. Nas et al 7 developed a simulation model to examine the effect of maritime traffic in a port on the NT. Shahpanah et al 9 focused on the waiting time of ships for towage operations in container terminals and attacked the queuing problem in towage operations by simulation to reduce the average waiting time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In one of the simulation studies focusing entirely on towage services, Nas 1 aimed to determine the optimum parking locations of tugboats belonging to an organization providing towage services in a port in Turkey. Nas et al 7 developed a simulation model to examine the effect of maritime traffic in a port on the NT. Shahpanah et al 9 focused on the waiting time of ships for towage operations in container terminals and attacked the queuing problem in towage operations by simulation to reduce the average waiting time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since ports/terminals have a complex structure, they are modeled and analyzed mostly with simulation techniques instead of analytical methods. [28][29][30][31] The ProModel simulation software, which was used in many studies 4,32,33 before and tested its reliability and validity in terms of performance and outputs, was used in this study.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…By giving pilotage and towage services to the ships whose service processes at the berths were completed, the ships are provided to leave the port. 4,5 Port capacity is generally related to the number of berths available to ship traffic and cargo handling capacity. It should be planned so as to ensure minimum waiting time of ships and maximum use of berth facilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it is observed that there are limited studies on tugboats, which is one of the most important types of service ship. The related literature on tugboats is generally on the problems of scheduling and allocation (Liu, 2009;Wang et al, 2012;Nas et al, 2016). There are also some studies on the selection and braking/towing force of tugboats (Yang et al, 2010;Çakíroglu et al, 2018;Balin et al, 2019).…”
mentioning
confidence: 99%